Evaluation of in Vitro Antimicrobial Effects of Aqueous Extract of Tribulus terrestris Against Oral Bacteria - Zahra Kiani; Pouria Mohammad Parast Tabas; khashayar khalilpour; Mahjoube Goldani Moghadam; Majid Zare_Bidaki (Medical Laboratory Journal, 2021)
Background and objectives: Medicinal plants have long been considered as one of the most important pillars of traditional medicine. Existing challenges in the treatment of diseases, particularly infectious diseases, are major drivers for herbal medicine studies. Tribulus terrestris has been widely used in traditional medicine to treat various diseases. This study aimed to investigate in vitro antibacterial effect of the aqueous extract of T. terrestris on several oral bacteria.